2023
DOI: 10.1097/ms9.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude toward COVID-19 booster dose among health care professionals in Nepal: a cross-sectional study

Abstract: Introduction: Vaccination has become the most effective way to combat the coronavirus disease 2019 (COVID-19) pandemic. As there have been reports of a gradual decline in the protection it offers, many countries have decided to administer booster doses of the COVID-19 vaccine. In Nepal, booster doses have been introduced to frontline health workers as a priority group. Therefore, this study aims to assess the knowledge and attitude of health care professionals toward booster doses of COVID-19 vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Overall practices' level toward HBV infection among MSs is high (53.1%). More than two-thirds of the students (68.3%) received the HBV vaccine before entering clinical practice similar to results of other studies conducted in Senegal and Saudi Arabia [21,28], but Jordanian MS's vaccine administration is less than their fellow students in Nepal and Iran [30,32], while around forty percent of MSs were screened for HBV before clinical practice [11]. Only 42.3% of MSs consistently use gloves before contacting patients or performing medical procedures, which is lower than a study conducted in Vietnam [25].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall practices' level toward HBV infection among MSs is high (53.1%). More than two-thirds of the students (68.3%) received the HBV vaccine before entering clinical practice similar to results of other studies conducted in Senegal and Saudi Arabia [21,28], but Jordanian MS's vaccine administration is less than their fellow students in Nepal and Iran [30,32], while around forty percent of MSs were screened for HBV before clinical practice [11]. Only 42.3% of MSs consistently use gloves before contacting patients or performing medical procedures, which is lower than a study conducted in Vietnam [25].…”
Section: Discussionsupporting
confidence: 84%
“…However, surprisingly, we have noticed that 44.1% of MSs claimed that HBV infection can be transmitted by sharing food and utensils. This is an alarming finding, which can have an impact on the level of stigma with encountering people who are infected by HBV, which has been reported by a study in Saudi Arabia among MSs [28], and a similar study in Iraq showed that MSs had a negative attitude regarding sitting and shaking hands with people who were infected by HBV [29], which is in contrast to Nepal study among undergraduate MSs [30]. In addition, a previous study in Jordan found a significant level of stigma among nurses while delivering care to a patient infected by HBV [31].…”
Section: Discussionmentioning
confidence: 77%
“…Most of the studies conducted on primer vaccination in Bangladesh reported that 60–80 % of people had positive attitudes to accept a COVID-19 vaccine [ [39] , [40] , [41] , [42] , [43] ]. Worldwide, numerous studies have investigated varied COVID-19 VBD acceptance across different sub-population groups, including 44.6 % university community in Jordan [ 26 ], 75.3 % university people in Italy [ 27 ], 58.28 % adult people in India [ 30 ], 78.66 % health professionals in Nepal [ 32 ], 87.8 % university community in Germany [ 45 ] , 74.5 % students and health professionals in Poland [ 46 ], 72.7 % university community in Belgium [ 47 ], 62 % adult in the USA [ 48 ], 87.6 % general people in Malaysia [ 53 ] , 93.7 % Chinese general people [ 54 ], 71 % adult poles in Poland [ 55 ], 76.8 % older citizen in China [ 56 ], and 71.1 % health care workers in Saudi Arabia [ 57 ], 77.76 % general people in Pakistan [ 58 ] and 73.8 % health personnel in Singapore [ 59 ] declared their willingness to boost 3rd dose vaccine against the COVID-19 pandemic. These findings are supportive to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Global disparities in COVID-19 VBD acceptance were well documented across the countries, particularly in under-developed countries, and peoples are still reluctant to administer COVID-19 VBD [ 25 , 26 ]. Although few researchers reported relatively low levels of COVID-19 VBD apprehension in developed [ [27] , [28] , [29] ] and developing countries [ [30] , [31] , [32] ], a significant variability in responding COVID-19 VBD was found across different societies within the country [ 33 ]. Worldwide, several multi-dimensional antecedents were associated with COVID-19 VBD receptivity including socio-economic (e.g., employment, education level, and income status), socio-demographic attributes (e.g., marital status, age, gender, and ethnicity), place of residency (e.g., urban, semi-urban/rural), vaccine-specific concerns (equal safety, efficacy, effectiveness and post-vaccination side effects) socio-psychological (e.g., anti-vaccination sentiment, perceived risk of contagion, self-efficacy, sense of control, and academic attainment), financial (e.g., income source, living status), environmental (e.g., information sufficiency, trust, communication), experiential (e.g., disease exposure, social influences, previous vaccination experiences, and a history of clinical studies) influenced VBD decision [ [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%